2003
DOI: 10.1105/tpc.012971
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of phyC Mutants in Arabidopsis Reveals Complex Crosstalk between Phytochrome Signaling Pathways

Abstract: Studies with mutants in four members of the five-membered Arabidopsis phytochrome (phy) family (phyA, phyB, phyD, and phyE) have revealed differential photosensory and/or physiological functions among them, but identification of a phyC mutant has proven elusive. We now report the isolation of multiple phyC mutant alleles using reverse-genetics strategies. Molecular analysis shows that these mutants have undetectable levels of phyC protein, suggesting that they are null for the photoreceptor. phyC mutant seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
183
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(197 citation statements)
references
References 76 publications
7
183
0
1
Order By: Relevance
“…Perhaps consistent with this is the fact that null mutants of these loci in Arabidopsis were not easily identified in genetic screens and the phenotypes of the monogenic mutants are not readily apparent (Aukerman et al, 1997;Devlin et al, 1998;Franklin et al, 2003;Monte et al, 2003). However, PHYC, D, and E have been retained much longer than the expected half-life of duplicate genes of ;3 to 7 million years (Lynch and Conery, 2000).…”
Section: Additional Phytochromes: An Expanded Role For the Phytochrommentioning
confidence: 68%
See 2 more Smart Citations
“…Perhaps consistent with this is the fact that null mutants of these loci in Arabidopsis were not easily identified in genetic screens and the phenotypes of the monogenic mutants are not readily apparent (Aukerman et al, 1997;Devlin et al, 1998;Franklin et al, 2003;Monte et al, 2003). However, PHYC, D, and E have been retained much longer than the expected half-life of duplicate genes of ;3 to 7 million years (Lynch and Conery, 2000).…”
Section: Additional Phytochromes: An Expanded Role For the Phytochrommentioning
confidence: 68%
“…Thus, phyB also is the primary mediator of shade avoidance, with additional light-stable forms in Arabidopsis, phyD and phyE, making lesser (Franklin, 2008) though perhaps important fine-tuning (Ballaré , 2009) contributions. The fourth light-stable form is phyC, a weak R sensor that functions in leaf development and perception of photoperiod Monte et al, 2003). As discussed later in the review, recent studies have revealed roles for phyC-E that were not apparent from the initial characterization of the phyC-E null mutants.…”
Section: Phytochrome Activities Under Canopies May Be Antagonisticmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypocotyl length and cotyledon opening were measured from at least 20 seedlings as described (Monte et al, 2003;Leivar et al, 2008a). Data were analyzed using Tukey's multiple comparison test (GraphPad Prism software) and/or Student's t test as indicated.…”
Section: Methods Plant Materials Seedling Growth and Measurementsmentioning
confidence: 99%
“…For RNA gel blot analysis, total RNA extraction, loading, and hybridization conditions were as described (Monte et al, 2003). Specific probe for PIF3 was prepared as described (Monte et al, 2004).…”
Section: Gene Expression Analysis By Qpcr and Rna Gel Blotsmentioning
confidence: 99%